The Exploration of Vetiver (Vetiveria zizanioides) as Co-Chemotherapy of Lung Cancer Selectively Targets AKR1C1: Bioinformatics Approach - Saputra, Lucky Octavianus; Fawzy, Salsabila Yusfita; Wardani, Ratih Kurnia; Lukitaningsih, Endang (Indonesian Society for Cancer Chemoprevention, 2022)
Reactive Oxygen Species (ROS) is one of the cancer-causing agents, one of which is lung cancer. In addition to being carcinogenic, ROS can also be used to kill cancer cells themselves, by increasing their levels to the threshold of apoptosis. Therefore, it is necessary to inhibit certain antioxidant enzymes that are highly expressed in lung cancer. One of them is AKR1C1 which plays a role in the eradication of intracellular ROS. However, AKR1C1 has a high structural similarity to AKR1C2, so it can inhibit therapy causing selectivity problems. Vetiver (Vetiveria zizanioides) has potential as an anticancer. This study was conducted to explore vetiver as a co-chemotherapeutic agent for lung cancer targeting AKR1C1 selectively. The method used is distillation, identification of vetiver compounds using GC-MS, and through bioinformatics studies. Predictive analysis with KNIME was carried out to determine the activity of the test compound. All tested vetiver compounds had a predictive value of 1 (active) on AKR1C1 and 0 (inactive) on AKR1C2. Through GC-MS obtained 354 compounds were identified. These compounds are used to filter the compounds predicted by KNIME. The molecular docking results showed that of the 10 tested vetiver compounds, there was 1 compound that had the strongest bond in interacting with AKR1C1, namely beta vetispirene compound with an S-score of -15.12 kcal/mol, and stronger than native ligand and aspirin. Based on the research data, it can be concluded that the beta vetispirene compound in vetiver can be a potential co-chemotherapy agent for lung cancer in targeting AKR1C1 selectively. However, further research is needed to prove its activity on lung cancer cells.Keywords: ROS (Reactive Oxygen Species), Lung Cancer, AKR1C1, selectivity, vetiver (Vetiveria zizanioides).